Management of rectal cancer: Times they are changing - Cravo,Marilia (2014)
Approximately one third of all colorectal malignancies are located in the rectum. It as long been recognized that rectal cancers behave differently from colonic tumors, namely in terms of local recurrence. For this reason, specific protocols have been developed to manage this disease both in staging procedures as well as in neoadjuvant and adjuvant chemoradiation treatments. Magnetic resonance imaging is now obligatory for rectal cancer staging. Also, preoperative chemoradiation is recommended in the large majority of locally advanced rectal cancers with obvious advantages in downstaging and downsizing tumors, sometimes allowing spincteric-sparing procedures. Total mesorectum excision is now the rule when operating on rectal cancer. Despite these advances, there are still unanswered questions, namely the utility of using neoadjuvant protocols in low lying, early stage tumors with the aim of performing a local excision procedure and the utility of re-staging the disease after neo-adjuvant treatment. In fact, response to neoadjuvant therapy may become a cornerstone of rectal cancer treatment and individualized therapy. Finally, there is the concern that with current protocols, we are overtreating some patients that would not need such extensive treatment. In this review, we critically examine recent advances in staging, surgery, and chemoradiation in the management of patients with rectal cancer which have not typically been incorporated in published treatment guidelines.